The venetian-blind effect: a preference for zero disparity or zero slant? - Vlaskamp, Björn N.; Guan, Phillip; Banks, Martin S. (Frontiers in Psychology, 2013)
When periodic stimuli, such as vertical sinewave gratings, are presented to the two eyes, the initial stage of disparity estimation yields multiple solutions stacked in at multiple depths. The solutions are all frontoparallel when the sinewaves have the same spatial frequency;. They are all slanted when the sinewaves have quite different frequencies. Despite the multiple solutions, humans perceive only one depth in each visual direction: a single frontoparallel plane when the frequencies are the same and a series of small slanted planes—Venetian blinds—when the frequencies are quite different. These percepts are consistent with a preference for solutions that minimize absolute disparity or that minimize overall slant. We conducted two psychophysical experiments to determine whether the preference is for minimum disparity or and for minimum slant are identical for gaze at zero eccentricity., We dissociated the predictions of the two by measuring the occurrence of Venetian blinds when the stimuli were viewed in eccentric gaze. The results were generally quite consistent with a zero-disparity preference (experiment 1), but we also observed a shift toward a zero-slant preference when the edges of the stimulus had zero slant (experiment 2). These observations provide useful insights into how the visual system constructs depth percepts from a multitude of possible depths.